The Role of Human Resource Management with Special Qualifications Provided for Enhancing the Quality of Higher Education in Kosovo - Nallbani, Shqiponja (Journal of Research in Educational Sciences, 2013)
Higher education is one of the essential components of social and political transformations, which also directly affect the steady state institutions and the creation of preconditions for economic development. As shown by the experiences of many other countries, university education helps in considerable degree in quality assurance frameworks and competitive labor market. Therefore the higher education system, the political and economic development is interrelated and interdependent. Higher education institutions have three main functions related: increasing function of knowledge and skills, the creation of staff function for labor market and social and political functions. But higher education system in Kosovo still continues to face fundamental problems that currently degrade this segment. The main problem is that he recorded with the level of quality of higher education is in fact a problem of the entire education system in the country. The reasons are many, but the lack of skilled human resources and competence is evident. This means that without a comprehensive reform of the education system, this segment is unlikely to reform desirable. Really saying, today, there are a series of guidance documents and recommended that are guiding the process of reforming the higher education system but we consider that action plan is missing related to lack of qualified human resources with experience who will manage these needs.